Chemical Probes for the Functionalization of Polyketide Intermediates1. Issue 44 (11th September 2014) - Riva, Elena; Wilkening, Ina; Gazzola, Silvia; Li, W. M. Ariel; Smith, Luke; Leadlay, Peter F.; Tosin, Manuela
Abstract A library of functionalized chemical probes capable of reacting with ketosynthase‐bound biosynthetic intermediates was prepared and utilized to explore in vivo polyketide diversification. Fermentation of ACP mutants of S. lasaliensis in the presence of the probes generated a range of unnatural polyketide derivatives, including novel putative lasalocid A derivatives characterized by variable aryl ketone moieties and linear polyketide chains (bearing alkyne/azide handles and fluorine) flanking the polyether scaffold. By providing direct information on microorganism tolerance and enzyme processing of unnatural malonyl‐ACP analogues, as well as on the amenability of unnatural polyketides to further structural modifications, the chemical probes constitute invaluable tools for the development of novel mutasynthesis and synthetic biology.